Analysis of Default in Cooperation Agreements: A Perspective on Rights and Obligations of The Parties In Dispute Resolution - Rayhan Fahriza Yose; Gunawan Djajaputra (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze defaults in cooperation agreements and examine the rights and obligations of the parties in dispute resolution. The urgency of this research arises from the increasing occurrence of defaults in cooperation agreements, which have significant legal and economic consequences for business relationships and economic stability. Using a normative juridical approach, the research examines provisions of the Indonesian Civil Code and relevant legal doctrines, focusing on dispute resolution mechanisms through litigation and alternative methods. Primary legal sources include the Civil Code (KUHPerdata), Law No. 30/1999 on Arbitration, and Supreme Court regulations, while secondary sources comprise legal journals and court decisions. The findings show that default in cooperation agreements results in legal consequences such as compensation, agreement termination, and performance enforcement. Several procedural conditions must be met, including the seriousness of the breach and timely legal action. The study provides a novel contribution by combining normative legal analysis with practical considerations in resolving contractual disputes within the Indonesian legal framework. It concludes that cooperation agreements must clearly define mutual obligations and dispute resolution procedures to ensure legal certainty and fairness. The research recommends that parties include specific clauses addressing default and adopt alternative dispute resolution mechanisms to reduce litigation and maintain business relationships.